2021
DOI: 10.1371/journal.pone.0250976
|View full text |Cite
|
Sign up to set email alerts
|

Rights based approaches to sexual and reproductive health in low and middle-income countries: A systematic review

Abstract: Introduction The Sustainable Development Goals, which are grounded in human rights, involve empowering women and girls and ensuring that everyone can access sexual and reproductive health and rights (Goal 5). This is the first systematic review reporting interventions involving rights-based approaches for sexual and reproductive health issues including gender-based violence, maternity, HIV and sexually transmitted infections in low and middle-income countries. Aims To describe the evidence on rights-based ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…10 Evidence suggests that most young people are not even aware of the extent to which their sexual rights are being violated; worse yet, they continue to be unaware of where they can turn for legal or social advice; 5 and the poor quality of rights-based interventions for sexual and reproductive health rights reported in low and middle-income countries like Ethiopia. 11 As a result, the issue continues to be a major concern for university students, with limited studies indicating that their knowledge of sexual and reproductive health rights is grossly inadequate. In Nepal, for example, the mean level of knowledge about reproductive and sexual health rights was barely more than fifty percent (51.12%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Evidence suggests that most young people are not even aware of the extent to which their sexual rights are being violated; worse yet, they continue to be unaware of where they can turn for legal or social advice; 5 and the poor quality of rights-based interventions for sexual and reproductive health rights reported in low and middle-income countries like Ethiopia. 11 As a result, the issue continues to be a major concern for university students, with limited studies indicating that their knowledge of sexual and reproductive health rights is grossly inadequate. In Nepal, for example, the mean level of knowledge about reproductive and sexual health rights was barely more than fifty percent (51.12%).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Evidence suggests that most young people are not even aware of the extent to which their sexual rights are being violated; worse yet, they continue to be unaware of where they can turn for legal or social advice; 5 and the poor quality of rights-based interventions for sexual and reproductive health rights reported in low and middle-income countries like Ethiopia. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Most reviews of structural interventions have focused on other aspects of sexual and reproductive health, particularly HIV prevention [ 8 , 43 , 44 , 45 , 46 , 47 ], as well as violence prevention [ 48 , 49 ] and child marriage prevention [ 50 ]. Reviews that focused on particular types of structural interventions tended to include only a minority or no studies measuring or focusing on contraceptive use [ 51 , 52 , 53 , 54 ] or did not focus on adolescents [ 11 , 55 , 56 , 57 ] or LMICs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…That there are methodological challenges in this field is not news. The need for consistent outcome measures and empowerment indicators [ 4 , 55 , 57 , 59 ], issues of the conceptualisations and terminology relating to structural interventions or empowerment [ 46 , 53 , 60 ] and study design challenges [ 4 , 43 , 61 ] have all been identified previously.…”
Section: Discussionmentioning
confidence: 99%
“…Educational intervention strategies for pregnant women, family members and HCPs to improve their clinical skills were a common intervention component. 32,[44][45][46]53,54 Lack of knowledge of the importance of seeking medical care during pregnancy and labour hinders women's health behaviours and the decision-making process. 84 However, an international survey of maternal health researchers suggests that the major challenge for improving maternal care is access to healthcare rather than women's knowledge of the importance for healthcare.…”
Section: Mechanismsmentioning
confidence: 99%